Memory and its Relations with Cronos and Kairós - Viola, Solon Eduardo Annes; Albuquerque, Paulo Peixoto de (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
The article intends to show the vibrant and constant relationship between memory and the experience of the present; taking care to bring memory, truth and justice closer to the contemporary assumptions of human rights. Based on an analysis of the resurgence of an ultra-conservative ideology in Brazil in the last decade, we seek to demonstrate the importance of not forgetting the recent past in the country to point out relevance and paths that expand our network of meanings, and help us to recognize the risk of present and future experiences that attempt to suppress political and civil rights.
Keywords: Memory; Human Rights: Cronos; Kairós.